Active surveillance of metastatic renal cell carcinoma: Results from a prospective observational study (MaRCC). Issue 13 (25th March 2021) - Harrison, Michael R.; Costello, Brian A.; Bhavsar, Nrupen A.; Vaishampayan, Ulka; Pal, Sumanta K.; Zakharia, Yousef; Jim, Heather S. L.; Fishman, Mayer N.; Molina, Ana M.; Kyriakopoulos, Christos E.; Tsao, Che‐Kai; Appleman, Leonard J.; et al.
Abstract : Background: Systemic therapy (ST) can be deferred in patients who have metastatic renal cell carcinoma (mRCC) and slow‐growing metastases. Currently, this subset of patients managed with active surveillance (AS) is not well described in the literature. Methods: This was a prospective observational study of patients with mRCC across 46 US community and academic centers. The objective was to describe baseline characteristics and demographics of patients with mRCC initially managed by AS, reasons for AS, and patient outcomes. Descriptive statistics were used to characterize demographics, baseline characteristics, and patient‐related outcomes. Wilcoxon 2‐sample rank‐sum tests and χ 2 tests were used to assess differences between ST and AS cohorts in continuous and categorical variables, respectively. Kaplan‐Meier survival curves were used to assess survival. Results: Of 504 patients, mRCC was initially managed by AS (n = 143) or ST (n = 305); 56 patients were excluded from the analysis. Disease was present in 69% of patients who received AS, whereas the remaining 31% had no evidence of disease. At data cutoff, 72 of 143 patients (50%) in the AS cohort had not received ST. The median overall survival was not reached (95% CI, 122 months to not estimable) in patients who received AS versus 30 months (95% CI, 25‐44 months) in those who received ST. Quality of life at baseline was significantly better in patients who were managed with AS versus ST. Conclusions: AS occurs frequently (32%) in real‐world clinical practice and appears to be a safe and appropriate alternative to immediate ST in selected patients. Abstract : This prospective observational study followed patients with metastatic renal cell carcinoma who were managed by active surveillance before treatment. The approach is used frequently in clinical practice and appears to be a safe and appropriate option for some patients.